Latvijos ir Lietuvos istoriografijos paralelės: bandymai bendradarbiauti ir problemos tarpukaryje - Šimkus, Robertas (Lietuvos istorijos studijos, 2007)
The object of this study is the links and cooperation between Latvian-Lithuanian historians. Presumptions of historiographic parallels are being ventilated in the study on institutional and individual basis so that the links between past Latvian-Lithuanian historians would be identified.The study describes the ways how cooperation of Lithuanian-Latvian historians was evidenced, when there were the most favourable circumstances: in the context of academic institutions' launching and practice. The reasons for national historiography's insularity are outlined, which did not enable the cooperation of academic historians to be developed. There are no specific cooperation facts highlighted in the study, but trends, the cooperation opportunities during the academic historiography genesis in Latvia and Lithuania (during interwar). The main Latvian-Lithuanian historiography trends presented in a study reflect well up till now characteristic institutional - academic, social indifference of Latvian-Lithuanian historiography.